Calvin and the Early Reformation - Brewer, Brian C. (Studies in Medieval and Reformation Traditions Ser., 2019)
"Those who have a passing knowledge of John Calvin's theology and reforms in Geneva in the sixteenth century may picture the confident and mature theologian and preacher without appreciating the various events, people, and circumstances that shaped the man. Before there was Protestantism's first and eminent systematic theologian, there was the French youth, the law student and humanist, the Protestant convert and homeless exile, the reluctant reformer and anguished city leader. Snapshots of the young Calvin create a collage that give a bigger picture to the grey-bearded Protestant reformer. Eleven scholars of early-modern history have joined in this volume to depict the people, movements, politics, education, sympathizers, nemeses, and controversies from which Calvin immerged in his young adulthood".